2016
DOI: 10.1038/srep26556
|View full text |Cite
|
Sign up to set email alerts
|

Network Signatures of IgG Immune Repertoires in Hepatitis B Associated Chronic Infection and Vaccination Responses

Abstract: The repertoire of IgG antibody responses to infection and vaccination varies depending on the characteristics of the immunogen and the ability of the host to mount a protective immune response. Chronic hepatitis B virus (HBV) infections are marked by persistent infection and immune tolerance to vaccination. This disease offers a unique opportunity to discover key repertoire signatures during infection and in response to vaccination. Complementarity determining region 3 of an antibody heavy chain (CDR-H3) has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Furthermore, the family source sequences and CDR3 sequences demonstrated heterogeneity [23]. Our findings also consistent with Chang’s report, they used HTS to characterize the H chain CDR3 sequences in paired siblings of 4 families in which only one member of each pair had chronic HBV infections, they reported that vaccination induced significant increases of H chain CDR3 cluster diversities among siblings without hepatitis B [24]. Our studies showed that the 3 healthy individuals shared a small number of CDR3 sequences before and after the immunization.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the family source sequences and CDR3 sequences demonstrated heterogeneity [23]. Our findings also consistent with Chang’s report, they used HTS to characterize the H chain CDR3 sequences in paired siblings of 4 families in which only one member of each pair had chronic HBV infections, they reported that vaccination induced significant increases of H chain CDR3 cluster diversities among siblings without hepatitis B [24]. Our studies showed that the 3 healthy individuals shared a small number of CDR3 sequences before and after the immunization.…”
Section: Discussionsupporting
confidence: 89%
“…The protocol in recruiting dengue subjects (Table 1 ; ND 5 , SD 1-7 , and HD 1-7 ) was approved by the Institutional Review Board of Kaohsiung Medical University Hospital. Some of non-dengue controls (Table 1 ; ND 1-4 ) were from a previous study ( 13 ), the protocol of which was approved by both the Institutional Review Board of National Health Research Institutes and the Institutional Review Board of En Chu Kong Hospital. Study methods were carried out in accordance with the relevant guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we adapted a selection heuristic of antibody repertoires that was developed to characterize carrier children of chronic hepatitis B and vaccination responses of healthy siblings on the platform of NGS ( 13 ). After reproducing the same result of the infection signature in the hepatitis B data set by the new pipeline, we applied the renewed scheme to a public data set of dengue fever from Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination provides a controlled and easily administered stimulus that can be used to study this complex system [7]. An increase in clonality has been observed in the post-vaccination BCR repertoire, which has been related to the proliferation of B cells and the production of active plasma cells [8][9][10][11][12][13][14]. An increase in the sequences shared between individuals, referred to as the public repertoire or stereotyped BCRs, has also been observed, and there is mounting evidence that this public repertoire is at least partly due to convergent evolution in different individuals responding to the same stimulus [10,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%